Startups and Digital Media : Gaining a Competitive Advantage - Habibli, Samir (2025)
Startups are increasingly using digital media in the digital age to build their brands, engage with customers, and gain a competitive advantage. This thesis explores how Azerbaijani startups are using digital platforms such as digital media and digital advertising to be more competitive in a market. The study uses a qualitative methodology that includes a practical experiment using Hellojob.az, a growing Azerbaijani business platform, and semi-structured interviews with representatives from seven startups across industries. In addition to identifying key platforms, the study examines the role of digital media in startup strategies and analyzes opportunities and challenges in the Azerbaijani entrepreneurial ecosystem. While the findings are region-specific, they provide insightful insights for startups in the region looking to successfully leverage digital media. The thesis concludes with tactical recommendations for business owners looking to enhance market positioning and expansion through creative use of digital media.